A negative electrode active material and its preparation method and application
By forming a polymer cladding with a unique hydrophilic structure on the surface of the silicon-carbon anode material, the poor dispersion and gas production of silicon-carbon anode material in water are solved, and the electrode sheet quality and battery performance are improved.
Patent Information
- Application Number
- CN202410618517.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-17
- Publication Date
- 2025-08-22
- Estimated Expiration
- 2044-05-17
AI Technical Summary
The existing silicon-carbon negative electrode active materials have poor dispersion in water, resulting in serious gas production, affecting the coating quality of the electrode sheet and reducing battery performance.
A polymer cladding layer composed of a specific proportion of binders and hydrophilic graft monomers is used to form a unique hydrophilic structure, inhibiting the hydrophilicity of silicon-carbon materials and improving their dispersion in water, reducing gas production during homogenization and electrode sheet coating.
It improves the dispersion of the negative electrode active material and the quality of the electrode sheet, reduces the gas production, and improves the safety and performance of the battery, including capacity, first effect and cycle stability.
Smart Images

Figure CN118572063B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode active material and a preparation method and application thereof. Background Art
[0002] Silicon, with its high theoretical specific capacity, is considered an ideal next-generation anode material. Silicon-based anode materials are mainly divided into: pure silicon materials, silicon-oxygen materials, silicon-carbon materials, and materials composited with silicon and other metal oxides.
[0003] Taking the core-shell structure of silicon-carbon negative electrode materials as an example, nano-silicon is deposited in a porous carbon substrate and carbon-coated on the surface. However, due to the imperfection of the current coating process and poor batch stability, some exposed silicon will inevitably exist on the surface of the carbon-coated silicon-carbon negative electrode active material. In the subsequent surface modification work, polymers containing functional groups such as carboxyl, amino, and hydroxyl groups are usually introduced for coating modification. On the one hand, polymers with such groups can form hydrogen bonds with the hydroxyl groups on the silicon surface, increasing the adhesion of the silicon-carbon negative electrode active material and facilitating the preparation of the electrode. On the other hand, since such groups have good hydrophilicity, they are conducive to improving the dispersibility of the silicon-carbon negative electrode active material in water and making the active material uniformly distributed on the electrode surface. However, when the exposed silicon on the surface of the silicon-carbon negative electrode active material comes into contact with water, obvious gas (hydrogen) production will occur, resulting in a huge safety hazard when the silicon-carbon negative electrode active material is homogenized. It will also affect the coating quality of the electrode, such as the appearance of pores, cracks, and powder loss, which greatly affects the battery performance. Summary of the Invention
[0004] Based on this, it is necessary to provide a negative electrode active material, a preparation method and an application thereof to address the above problems; the polymer coating layer on the surface of the negative electrode active material has a unique hydrophilic and hydrophobic structure, which can not only be evenly dispersed in water, but also significantly reduces the gas production problem during the slurrying of the negative electrode active material and the coating of the electrode, thereby improving the quality of the electrode and the performance of the battery.
[0005] A negative electrode active material comprises a silicon-carbon material and a polymer coating layer coated on the surface of the silicon-carbon material, wherein the polymer coating layer comprises a binder and a hydrophilic grafting monomer;
[0006] The side chain of the binder contains an end group capable of forming a hydrogen bond; any end group in the hydrophilic grafted monomer structure contains a reactive group; the minimum unit repetition number of the segment not containing the end group in the side chain structure of the binder is n1, the minimum unit repetition number of the segment not containing the reactive group in the hydrophilic grafted monomer structure is n2, and n1 / n2 is 1.5-9.5.
[0007] In one embodiment, the side chain structure of the binder comprises a hydrophobic segment;
[0008] And / or, the binder is connected to the hydrophilic grafting monomer via a chemical bond.
[0009] In one embodiment, the structural formula of the binder is as shown in formula (1), Wherein, R1 is a hydrophobic segment, R2 is a group capable of forming a hydrogen bond with a silanol group, and n=100-800;
[0010] And / or, the structural formula of the hydrophilic grafting monomer is as shown in formula (2), Among them, R3 can produce a grafting reaction with R2, and R4 is a hydrophilic segment;
[0011] And / or, n1 / n2 is 1.5-5.
[0012] In one embodiment, in the structure of the binder, R1 is selected from substituted or unsubstituted alkyl chains, substituted or unsubstituted siloxane chains, wherein the substituent is selected from C1-C 20 Fatty alkyl, C4-C8 cycloalkyl, C2-C 15 an alkenyl group, an aromatic ring group or a fluorine atom;
[0013] And / or, R2 is selected from a carbonyl group and its derivative groups, a hydroxyl group, an amino group, a phosphate group, a thiol group, an aromatic group, an ether group, an ester group or a halogen atom.
[0014] In one embodiment, the binder is selected from at least one of polyvinyl acetic acid, poly (9-decenoic acid), and poly (2,2-tricosenoic acid).
[0015] In one embodiment, in the structure of the hydrophilic grafting monomer, R3 is selected from a thiol group, an acyl chloride group, a urea group, a hydroxyl group, a primary amine group, a secondary amine group, or a tertiary amine group;
[0016] And / or, R4 is selected from a substituted or unsubstituted ether chain, a substituted or unsubstituted amide chain, wherein the substituent is selected from an amino group, a carboxyl group, a hydroxyl group, a thiol group, a urea group, an amide group or a hydrazine group.
[0017] In one embodiment, the hydrophilic grafting monomer is selected from at least one of diethylene glycol monomethyl ether, tetraethyl glycol monomethyl ester, 2,5,8,11,14-pentaoxa-16-hexadecanol, undecaprylyl glycol monomethyl ether, and 1-(2-aminoethoxy)-2-methoxyethane.
[0018] In one embodiment, the polymer coating layer further includes a conductive agent.
[0019] In one embodiment, the silicon-carbon material is a composite material of porous carbon and nano-silicon, wherein the D min Greater than 0.3 μm, D 10 Greater than 1.5μm, D 50 3.5μm-7μm, D 90 Less than 9μm, D max Less than 12μm, (D 90 -D 10 ) / D 50 Less than 1.1, average pore size 5nm-40nm;
[0020] And / or, the median particle size of the silicon-carbon material is 5 μm-15 μm, and the particle size concentration is 0.5-1.5;
[0021] And / or, the carbon content of the silicon-carbon material is 40%-60%;
[0022] And / or, the specific surface area of the silicon-carbon material is 1.5m 2 / g-5m 2 / g;
[0023] And / or, the resistivity of the silicon-carbon material is 2Ω·cm-10Ω·cm.
[0024] A method for preparing the negative electrode active material as described above comprises: dispersing a silicon-carbon material, a binder, and a hydrophilic grafting monomer in a solvent to obtain a mixture, and drying the mixture to obtain the negative electrode active material.
[0025] In one embodiment, the molar ratio of the side chain end groups of the binder to the hydrophilic grafting monomer is 1:0.2-1:1;
[0026] and / or, the solid content of the mixture is 3%-40%;
[0027] And / or, the mixture further includes a conductive agent;
[0028] And / or, the drying method is selected from at least one of hot air drying, spray drying or vacuum drying;
[0029] And / or, the drying temperature is 90°C-180°C.
[0030] A negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer, wherein the negative electrode active material layer comprises the negative electrode active material as described above.
[0031] A battery comprises the negative electrode sheet as described above.
[0032] The surface of the negative electrode active material described in the present invention has a polymer coating layer with a unique hydrophilic and hydrophobic structure. The polymer coating layer is composed of a specific binder and a specific hydrophilic grafted monomer, and satisfies a specific ratio of hydrophobic segments to hydrophilic segments. On the one hand, the polymer coating layer can inhibit the hydrophilicity of the silicon-carbon material, while improving the hydrophilicity of the negative electrode active material, so that the negative electrode active material not only has excellent dispersibility during the slurry and electrode coating process, but also reduces the gas production of the negative electrode active material during the slurry process, thereby improving the preparation safety and improving the electrode quality, thereby reducing the risk of falling off and peeling of the negative electrode active material on the electrode surface; on the other hand, the polymer coating layer can also inhibit the volume expansion of the silicon-carbon material and reduce the direct contact between the silicon-carbon material and the electrolyte, thereby improving the adaptability of the components in the battery, which is beneficial to improving the capacity, first effect and cycle stability.
[0033] Therefore, the negative electrode active material provided by the present invention can not only be evenly dispersed in water, but also significantly reduces the gas generation problem during the negative electrode active material slurrying and pole piece coating process, thereby improving the quality of the pole piece and the performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0035] Figure 1 This is a scanning electron microscope image of the negative electrode active material prepared in Example 1. DETAILED DESCRIPTION
[0036] To facilitate understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the technical field of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments or embodiments and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, including any two related listed items, any more related listed items, or the combination of all related listed items.
[0038] The present invention provides a negative electrode active material, comprising a silicon-carbon material and a polymer coating layer coated on the surface of the silicon-carbon material, wherein the material of the polymer coating layer comprises a binder and a hydrophilic grafting monomer.
[0039] The side chain of the binder contains an end group capable of forming a hydrogen bond; any end group in the hydrophilic grafted monomer structure contains a reactive group; the minimum unit repetition number of the segment not containing the end group in the side chain structure of the binder is n1, the minimum unit repetition number of the segment not containing the reactive group in the hydrophilic grafted monomer structure is n2, and n1 / n2 is 1.5-9.5.
[0040] The surface of the negative electrode active material described in the present invention has a polymer coating layer with a unique hydrophilic and hydrophobic structure. The polymer coating layer is composed of a specific binder and a specific hydrophilic grafted monomer, and satisfies a specific ratio of hydrophobic segments to hydrophilic segments. On the one hand, the polymer coating layer can inhibit the hydrophilicity of the silicon-carbon material, while improving the hydrophilicity of the negative electrode active material, so that the negative electrode active material not only has excellent dispersibility during the slurry and electrode coating process, but also reduces the gas production of the negative electrode active material during the slurry process, thereby improving the preparation safety and improving the electrode quality, thereby reducing the risk of falling off and peeling of the negative electrode active material on the electrode surface; on the other hand, the polymer coating layer can also inhibit the volume expansion of the silicon-carbon material and reduce the direct contact between the silicon-carbon material and the electrolyte, thereby improving the adaptability of the components in the battery, which is beneficial to improving the capacity, first effect and cycle stability.
[0041] Therefore, the negative electrode active material provided by the present invention can not only be evenly dispersed in water, but also significantly reduces the gas generation problem during the negative electrode active material slurrying and pole piece coating process, thereby improving the quality of the pole piece and the performance of the battery.
[0042] In one embodiment, n1 / n2 includes but is not limited to any one of 1.5, 1.75, 1.82, 3.5, 4, 4.86, 5, 5.6, 6, 6.5, 7.2, 7.8, 8, 8.5, 8.8, 8.9, 9 or a range between any two of them, more preferably 1.5-5.
[0043] In one embodiment, the terminal groups in the binder are selected from carbonyl groups and their derivatives, hydroxyl groups, amino groups, phosphate groups, thiol groups, aromatic groups, ether groups, ester groups or halogen atoms. Preferably, the terminal groups are selected from carbonyl groups and their derivatives, hydroxyl groups, and amino groups. More preferably, the terminal groups are selected from carboxyl groups, hydroxyl groups, and amino groups.
[0044] In one embodiment, the side chain structure of the binder further comprises a hydrophobic segment, preferably, the hydrophobic segment is selected from a substituted or unsubstituted alkyl chain, a substituted or unsubstituted siloxane chain, wherein the substituent is selected from C1-C 20 Fatty alkyl, C4-C8 cycloalkyl, C2-C 15 an alkenyl group, an aromatic ring group or a fluorine atom.
[0045] In one embodiment, the hydrophilic grafting monomer comprises a hydrophilic group and / or a hydrophilic element, wherein the hydrophilic group comprises a thiol group, an acyl chloride group, a urea group, a hydroxyl group, a primary amine group, a secondary amine group or a tertiary amine group, and the hydrophilic element comprises an oxygen, nitrogen, sulfur or halogen atom.
[0046] In one embodiment, the reactive group in the hydrophilic grafting monomer is selected from a thiol group, an acyl chloride group, a urea group, a hydroxyl group, a primary amine group, a secondary amine group, or a tertiary amine group.
[0047] In one embodiment, the binder is connected to the hydrophilic grafting monomer via a chemical bond, which is more conducive to forming a unique hydrophilic and hydrophobic structure of the polymer coating layer.
[0048] In one embodiment, the structural formula of the binder is as shown in formula (1), Wherein, R1 is a hydrophobic segment, R2 is a group capable of forming a hydrogen bond with a silanol group, and n = 100-800. It is understood that when the structural formula of the binder is formula (1), the repetition number of the minimum repeating unit of R1 is n1.
[0049] Preferably, R1 is selected from substituted or unsubstituted alkyl chains, substituted or unsubstituted siloxane chains, wherein the substituent is selected from C1-C 20 Fatty alkyl, C4-C8 cycloalkyl, C2-C 15 an alkenyl group, an aromatic ring group or a fluorine atom.
[0050] Preferably, R2 is selected from a carbonyl group and its derivative groups, a hydroxyl group, an amino group, a phosphate group, a thiol group, an aromatic group, an ether group, an ester group or a halogen atom. It is understood that the derivative groups of the carbonyl group include an aldehyde group, a carboxyl group and a ketone group, and the halogen atoms include F, Cl, Br, and I.
[0051] More preferably, R2 is selected from carbonyl and its derivatives, hydroxyl, and amino.
[0052] More preferably, R2 is selected from carboxyl, hydroxyl, and amino.
[0053] Specifically, the binder is selected from at least one of polyvinyl acetic acid, poly (9-decenoic acid), and poly (2,2-tricosenoic acid).
[0054] In one embodiment, the hydrophilic grafting monomer has a structural formula as shown in formula (2), Wherein, R3 can produce a grafting reaction with R2, and R4 is a hydrophilic segment. It can be understood that when the structural formula of the hydrophilic grafting monomer is formula (2), the repetition number of the minimum repeating unit of R4 is n2.
[0055] Preferably, R3 is selected from a mercapto group, an acyl chloride group, a urea group, a hydroxyl group, a primary amine group, a secondary amine group or a tertiary amine group.
[0056] Preferably, R4 is selected from a substituted or unsubstituted ether chain, a substituted or unsubstituted amide chain, wherein the substituent is selected from an amino group, a carboxyl group, a hydroxyl group, a thiol group, a urea group, an amide group or a hydrazine group.
[0057] Specifically, the hydrophilic grafting monomer is selected from at least one of diethylene glycol monomethyl ether (CAS: 111-77-3), tetraethyl glycol monomethyl ester (CAS: 23783-42-8), 2,5,8,11,14-pentaoxa-16-hexadecanol (CAS: 23778-52-1), undecanedelcol monomethyl ether (CAS: 114740-40-8), and 1-(2-aminoethoxy)-2-methoxyethane (CAS: 31576-51-9).
[0058] In one embodiment, the negative electrode active material and water are mixed to form an aqueous slurry with a solid content of 6% to 40%, and the absolute value of the Zeta potential of the slurry is 27.5 mV to 35.5 mV.
[0059] In one embodiment, the polymer coating layer further includes a conductive agent, wherein the conductive agent includes but is not limited to at least one of graphene, acetylene black, carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes, flake graphite, polyaniline, polypyrrole, polyacetylene, polythiophene, and poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS).
[0060] In one embodiment, the silicon-carbon material is a composite material of porous carbon and nano-silicon, wherein the D min Greater than 0.3 μm, D 10 Greater than 1.5 μm, D 50 3.5μm-7μm, D 90 Less than 9μm, Dmax Less than 12μm, (D 90 -D 10 ) / D 50 Less than 1.1, and the average pore size is 5nm-40nm.
[0061] Preferably, the median particle size of the silicon-carbon material is 5 μm-15 μm, including but not limited to any one of 5 μm, 8 μm, 10 μm, 12 μm, 15 μm or a range of values between any two of them; the particle size concentration is 0.5-1.5, including but not limited to any one of 0.5, 0.6, 1.0, 1.2, 1.5 or a range of values between any two of them.
[0062] Preferably, the carbon content of the silicon-carbon material is 40%-60%, including but not limited to any one of 40%, 45%, 50%, 55%, and 60%, or a range between any two of them.
[0063] Preferably, the specific surface area of the silicon-carbon material is 1.5 m 2 / g-5m 2 / g, including but not limited to 1.5m 2 / g, 2.0m 2 / g, 2.5m 2 / g, 3.0m 2 / g, 3.5m 2 / g, 4.0m 2 / g, 4.5m 2 / g、5m 2 / g, or any range of values between them.
[0064] Preferably, the resistivity of the silicon-carbon material is 2Ω·cm-10Ω·cm, including but not limited to any one of 2Ω·cm, 3Ω·cm, 4Ω·cm, 5Ω·cm, 6Ω·cm, 7Ω·cm, 8Ω·cm, 9Ω·cm, and 10Ω·cm, or a range between any two of them.
[0065] The present invention provides a method for preparing the negative electrode active material as described above, comprising: dispersing a silicon-carbon material, a binder, and a hydrophilic grafting monomer in a solvent to obtain a mixture, and drying the mixture to obtain the negative electrode active material.
[0066] It should be noted that the present invention does not limit the order of adding the silicon-carbon material, the binder and the hydrophilic grafting monomer. It is preferred to first disperse the binder and the hydrophilic grafting monomer in the solvent to form a uniform coating slurry, and then add the silicon-carbon material, which is more conducive to obtaining a uniform and dense coating layer structure.
[0067] In one embodiment, the molar ratio of the side chain end groups of the binder to the hydrophilic grafting monomer is 1:0.2-1:1, including but not limited to any one of 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1 or a range between any two of them.
[0068] In one embodiment, the solid content of the mixture is 3%-40%, including but not limited to any one of 3%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40% or any range between two of them.
[0069] In one embodiment, the solvent includes at least one of N-methylpyrrolidone, acetone, N,N-dimethylformamide, water, dimethyl sulfoxide, tetrahydrofuran, dichloromethane, methanol or ethanol.
[0070] In one embodiment, the mixture further includes a conductive agent, wherein the conductive agent includes but is not limited to at least one of graphene, acetylene black, carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes, flake graphite, polyaniline, polypyrrole, polyacetylene, polythiophene, and poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS).
[0071] In one embodiment, the drying method is selected from at least one of hot air drying, spray drying or vacuum drying.
[0072] In one embodiment, the drying temperature is 90°C-180°C, including but not limited to any one of 90°C, 100°C, 120°C, 140°C, 160°C, and 180°C, or a range between any two of them.
[0073] The present invention also provides a negative electrode sheet. The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer, wherein the negative electrode active material layer includes the negative electrode active material described above. It is understood that the negative electrode active material layer may also include materials such as a binder, which is not limited by the present invention.
[0074] The present invention also provides a battery. The battery includes the negative electrode sheet described above. It is understood that the battery also includes a positive electrode sheet, a separator, and an electrolyte, which are not limited in the present invention.
[0075] The negative electrode active material, its preparation method, and its application are further described below through the following specific examples. However, those skilled in the art will understand that the following examples are merely illustrative of the present invention and should not be construed as limiting the scope of the present invention. Where specific conditions are not specified in the examples, conventional conditions or those recommended by the manufacturer were followed. Reagents or instruments used, for which the manufacturer is not specified, are commercially available conventional products.
[0076] It should be noted that the silicon carbon materials used in the examples and comparative examples were purchased from Zhejiang Lichen Technology New Materials Co., Ltd., model C ONE-SC 1800, with a particle size of about 3 μm-7 μm and a specific surface area of about 3 m 2 / g, the carbon content is about 51.23%, and the resistivity is about 4.63Ω·cm.
[0077] It should be noted that the binder poly (9-decenoic acid) used in the examples and comparative examples has a monomer structure of (CAS: 14436-32-9); The preparation method of the polymer is a free radical polymerization method commonly understood by those skilled in the art, that is, the same as the preparation method of polyacrylic acid, and the degree of polymerization of the finally obtained poly (9-decenoic acid) is n = 560. Similarly, the monomer structure of the poly (22-tricosenoic acid) binder is (CAS: 65119-95-1), the degree of polymerization of the polymer is n = 600; the monomer structure of the polyvinyl acetate binder is (CAS: 625-38-7), the degree of polymerization of the polymer is n=480.
[0078] Example 1
[0079] Take 0.5g of conductive carbon black and add it to 300mL of water, set the stirring speed to 400rpm, stir for 2h, then add 30mmol of poly(9-decenoic acid) binder containing carboxyl groups and 30mmol of diethylene glycol monomethyl ether hydrophilic grafting monomer, set the stirring speed to 600rpm, stir for 1h to obtain a coating slurry. Slowly add 97.5g of silicon-carbon material to the coating slurry, set the stirring speed to 1000rpm, stir for 5h, and obtain a mixture with a solid content of 26.24%. Then add 1600mL of water to the mixture, set the stirring speed to 500rpm, stir for 0.5h, and obtain a mixture with a solid content of 5.32%.
[0080] The obtained mixture was dried by spray drying at a drying temperature of 170°C and a feed rate of 600 mL / h to obtain a negative electrode active material. The negative electrode active material obtained in this embodiment was subjected to morphology testing, and the results were as follows: Figure 1 shown.
[0081] Example 2
[0082] Take 0.5g of conductive carbon black and add it to 300mL of water, set the stirring speed to 400rpm, stir for 2h, then add 30mmol of poly(9-decenoic acid) binder containing carboxyl groups and 30mmol of tetraethyl glycol monomethyl ester hydrophilic grafting monomer, set the stirring speed to 600rpm, stir for 1h to obtain a coating slurry. Slowly add 97.5g of silicon-carbon material to the coating slurry, set the stirring speed to 1000rpm, stir for 5h, and obtain a mixture with a solid content of 26.71%. Then add 1600mL of water to the mixture, set the stirring speed to 500rpm, stir for 0.5h, and obtain a mixture with a solid content of 5.44%.
[0083] The obtained mixture was dried by spray drying, with the drying temperature set at 170° C. and the feeding rate set at 600 mL / h to obtain a negative electrode active material.
[0084] Example 3
[0085] Take 0.5g of conductive carbon black and add it to 300mL of water, set the stirring speed to 400rpm, stir for 2h, then add 30mmol of poly(2,2-tricosenoic acid) binder containing carboxyl groups and 30mmol of tetraethyl glycol monomethyl ester hydrophilic grafting monomer, set the stirring speed to 600rpm, stir for 1h to obtain a coating slurry. Slowly add 97.5g of silicon-carbon material to the coating slurry, set the stirring speed to 1000rpm, stir for 5h, and obtain a mixture with a solid content of 27.68%. Then add 1600mL of water to the mixture, set the stirring speed to 500rpm, stir for 0.5h, and obtain a mixture with a solid content of 5.70%.
[0086] The obtained mixture was dried by spray drying, with the drying temperature set at 170° C. and the feeding rate set at 600 mL / h to obtain a negative electrode active material.
[0087] Example 4
[0088] 0.5g of conductive carbon black was added to 300mL of water, stirred at 400rpm for 2h, followed by addition of a 30mmol carboxyl-containing poly(2,2-tricosenoic acid) binder and 30mmol of a 2,5,8,11,14-pentaoxa-16-hexadecanol hydrophilic grafting monomer. The mixture was stirred at 600rpm for 1h to obtain a coating slurry. 97.5g of silicon-carbon material was slowly added to the coating slurry, stirred at 1000rpm for 5h to obtain a mixture with a solid content of 27.91%. 1600mL of water was then added to the mixture, stirred at 500rpm for 0.5h to obtain a mixture with a solid content of 5.76%.
[0089] The obtained mixture was dried by spray drying, with the drying temperature set at 170° C. and the feeding rate set at 600 mL / h to obtain a negative electrode active material.
[0090] Example 5
[0091] Take 0.5g of conductive carbon black and add it to 300mL of water. Set the stirring speed to 400rpm and stir for 2h. Then add 30mmol of poly(2,2-tricosenoic acid) binder containing carboxyl groups and 30mmol of undecyl glycol monomethyl ether hydrophilic grafting monomer. Set the stirring speed to 600rpm and stir for 1h to obtain a coating slurry. Slowly add 97.5g of silicon-carbon material to the coating slurry, set the stirring speed to 1000rpm and stir for 5h to obtain a mixture with a solid content of 29.25%. Then add 1600mL of water to the mixture, set the stirring speed to 500rpm and stir for 0.5h to obtain a mixture with a solid content of 6.13%.
[0092] The obtained mixture was dried by spray drying, with the drying temperature set at 170° C. and the feeding rate set at 600 mL / h to obtain a negative electrode active material.
[0093] Example 6
[0094] Take 0.5g of conductive carbon black and add it to 300mL of water, set the stirring speed to 400rpm, stir for 2h, then add 30mmol of poly(9-decenoic acid) binder containing carboxyl groups and 30mmol of 1-(2-aminoethoxy)-2-methoxyethane hydrophilic grafting monomer, set the stirring speed to 600rpm, stir for 1h to obtain a coating slurry. Slowly add 97.5g of silicon-carbon material to the coating slurry, set the stirring speed to 1000rpm, stir for 5h, and obtain a mixture with a solid content of 26.21%. Then add 1600mL of water to the mixture, set the stirring speed to 500rpm, stir for 0.5h, and obtain a mixture with a solid content of 5.31%.
[0095] The obtained mixture was dried by spray drying, with the drying temperature set at 170° C. and the feeding rate set at 600 mL / h to obtain a negative electrode active material.
[0096] Example 7
[0097] Take 0.3g of conductive carbon black and add it to 300mL of water, set the stirring speed to 400rpm, stir for 2h, then add 25mmol of polyvinyl acetate binder containing carboxyl groups and 18mmol of diethylene glycol monomethyl ether hydrophilic grafting monomer, set the stirring speed to 600rpm, stir for 1h to obtain a coating slurry. Slowly add 120g of silicon-carbon material to the coating slurry, set the stirring speed to 1000rpm, stir for 5h, and obtain a mixture with a solid content of 29.35%. Then add 1700mL of water to the mixture, set the stirring speed to 500rpm, stir for 0.5h, and obtain a mixture with a solid content of 5.87%.
[0098] The obtained mixture was dried by vacuum drying at a drying temperature of 150° C. to obtain a negative electrode active material.
[0099] Comparative Example 1
[0100] Take 0.5g of conductive carbon black and add it to 300mL of water, set the stirring speed to 400rpm, stir for 2h, then add a polyvinyl acetate binder containing 30mmol of carboxyl groups, set the stirring speed to 600rpm, and stir for 1h to obtain a coating slurry. Slowly add 97.5g of silicon-carbon material to the coating slurry, set the stirring speed to 1000rpm, and stir for 5h to obtain a mixture with a solid content of 25.11%. Then add 1600mL of water to the mixture, set the stirring speed to 500rpm, and stir for 0.5h to obtain a mixture with a solid content of 5.02%.
[0101] The obtained mixture was dried by spray drying, with the drying temperature set at 170° C. and the feeding rate set at 600 mL / h to obtain a negative electrode active material.
[0102] Comparative Example 2
[0103] Take 0.5g of conductive carbon black and add it to 300mL of water. Set the stirring speed to 400rpm and stir for 2h. Then add 30mmol of poly(9-decenoic acid) binder containing carboxyl groups and 30mmol of 2,5,8,11,14-pentaoxa-16-hexadecanol hydrophilic grafting monomer. Set the stirring speed to 600rpm and stir for 1h to obtain a coating slurry. Slowly add 97.5g of silicon-carbon material to the coating slurry, set the stirring speed to 1000rpm and stir for 5h to obtain a mixture with a solid content of 26.95%. Then add 1600mL of water to the mixture, set the stirring speed to 500rpm and stir for 0.5h to obtain a mixture with a solid content of 5.50%.
[0104] The obtained mixture was dried by spray drying, with the drying temperature set at 170° C. and the feeding rate set at 600 mL / h to obtain a negative electrode active material.
[0105] Comparative Example 3
[0106] Take 0.5g of conductive carbon black and add it to 300mL of water, set the stirring speed to 400rpm, stir for 2h, then add 30mmol of poly(9-decenoic acid) binder containing carboxyl groups and 30mmol of 11ethylene glycol monomethyl ether hydrophilic grafting monomer, set the stirring speed to 600rpm, stir for 1h to obtain a coating slurry. Slowly add 97.5g of silicon-carbon material to the coating slurry, set the stirring speed to 1000rpm, stir for 5h, and obtain a mixture with a solid content of 28.33%. Then add 1600mL of water to the mixture, set the stirring speed to 500rpm, stir for 0.5h, and obtain a mixture with a solid content of 5.87%.
[0107] The obtained mixture was dried by spray drying, with the drying temperature set at 170° C. and the feeding rate set at 600 mL / h to obtain a negative electrode active material.
[0108] Comparative Example 4
[0109] Take 0.5g of conductive carbon black and add it to 300mL of water, set the stirring speed to 400rpm, stir for 2h, then add 30mmol of poly(2,2-tricosenoic acid) binder containing carboxyl groups and 30mmol of diethylene glycol monomethyl ether hydrophilic grafting monomer, set the stirring speed to 600rpm, stir for 1h to obtain a coating slurry. Slowly add 97.5g of silicon-carbon material to the coating slurry, set the stirring speed to 1000rpm, stir for 5h, and obtain a mixture with a solid content of 27.21%. Then add 1600mL of water to the mixture, set the stirring speed to 500rpm, stir for 0.5h, and obtain a mixture with a solid content of 5.57%.
[0110] The obtained mixture was dried by spray drying, with the drying temperature set at 170° C. and the feeding rate set at 600 mL / h to obtain a negative electrode active material.
[0111] The negative electrode active materials prepared in Examples 1-7 and Comparative Examples 1-4 were subjected to characterization tests, and the test results are shown in Table 1.
[0112] (1) The test method for the water volatilization rate includes: weighing 10 g of the negative electrode active material and placing it in a 100 mL beaker with a diameter of 50 mm; adding 70 g of deionized water to the beaker and stirring it at room temperature for 30 min using a magnetic stirrer to ensure that the negative electrode active material and water are fully mixed to form a uniform aqueous slurry; placing the prepared aqueous slurry in an oven at 100°C and heating it for 5 h; after heating, recording and weighing the mass of the remaining slurry in the beaker to calculate the water volatilization rate; calculating the water volatilization rate based on the relationship between the water volatilization rate and time.
[0113] (2) The dispersibility test method includes: weighing 5g of negative electrode active material and placing it in 60mL of deionized water for stirring and dispersion to form a slurry, and performing potential analysis on it using a BeNano 90 Zeta potential analyzer. The test results are expressed as the absolute value of Zeta potential. It should be noted that Zeta potential can be used to measure the strength of mutual repulsion or attraction between particles. When the absolute value of Zeta potential (positive or negative) is higher, it means that the system is more stable, that is, the dissolution or dispersion can resist aggregation; when the absolute value of Zeta potential (positive or negative) is lower, it means that the system is more inclined to coagulation or aggregation, that is, the attraction exceeds the repulsion, the dispersion is destroyed and coagulation or aggregation occurs. In this dispersibility test, when the absolute value of Zeta potential is in the range of 20-50mV, the larger the absolute value, the higher the dispersion stability; and when the absolute value of Zeta potential is less than 20mV, it means that the system is easy to coagulate and the dispersibility is poor.
[0114] Table 1
[0115]
[0116] The negative electrode active materials prepared in Examples 1-7 and Comparative Examples 1-4 were subjected to gas generation test, buckling test and soft pack battery test.
[0117] (1) The gas production test method includes: taking 5g of negative electrode active material and 150g of water into a sealed bottle, fully dissolving them by centrifugal stirring, and then standing in a constant temperature chamber at 25°C. The gas production (H2) in the bottle on the first day, the second day, and the third day is tested respectively (here X day represents the gas production on the Xth day). The test results are shown in Table 2.
[0118] (2) The charge-withdrawal test method includes: preparing an electrode sheet with the negative electrode active material, SP, CMC, and PAA in a ratio of 80:10:5:5, using lithium metal as the counter electrode, LiPF6 as the lithium salt, a mixed solvent of EC and DEC with a volume ratio of 1:1 as the electrolyte solvent, and Celgard2400 membrane as the separator to prepare a Li / Si half-cell, and testing its first coulombic efficiency and charge specific capacity. The test conditions are: voltage 0.005V-1.5V, charge and discharge 0.1C / 0.1C, and the test results are shown in Table 3.
[0119] (3) The soft-pack battery test method includes: using 80% artificial graphite doped in the negative electrode active material as the negative electrode, using NCM111 ternary material as the positive electrode material, using LiPF6 as the lithium salt, using a mixed solvent of EC and DEC with a volume ratio of 1:1 as the electrolyte solvent, and using Celgard2400 membrane as the separator, to prepare a soft-pack lithium-ion battery, and performing a cycle test (300 cycles of capacity retention) under the test conditions: voltage 2.5V-4.2V, charge and discharge 1C / 1C. The cycle test results are shown in Table 3.
[0120] Table 2
[0121]
[0122] Note: The gas production value of each sample is the maximum value among the corresponding three values. For example, the gas production value of comparative example 1 is 4.69CC / kg.
[0123] Table 3
[0124]
[0125]
[0126] According to Table 1 and Table 2, combined with Examples 1-7 and Comparative Examples 1-4, it can be seen that the larger the n1 / n2 value is, the stronger the hydrophobicity of the negative electrode active material is and the less gas production is.
[0127] According to Table 1 and Table 3, combined with Examples 1-7 and Comparative Examples 1-4, it can be seen that by regulating the n1 / n2 value of the polymer coating layer, the hydrophobicity of the negative electrode active material was successfully improved, thereby improving the charge capacity, initial coulombic efficiency, and electrochemical stability of the negative electrode active material. This is attributed to the fact that after improving the gas production problem of the negative electrode active material, the process of homogenization and coating the electrode sheet was optimized, thereby bringing about an improvement in electrochemical performance. However, due to the excessive hydrophobicity of Comparative Example 4, process problems such as uneven dispersion occurred during homogenization, which affected the quality of the electrode sheet and the battery. Therefore, n1 / n2 must meet the range defined by the present invention to effectively improve the electrochemical performance of the negative electrode active material.
[0128] Comparison of Example 1 and Example 6 shows that the types of reactive groups in the cross-linked grafting of the binder and the hydrophilic grafting monomer do not significantly affect the hydrophilicity or hydrophobicity of the grafted binder.
[0129] In summary, the surface of the negative electrode active material provided by the present invention has a polymer coating layer with a unique hydrophilic and hydrophobic structure, which meets the specific ratio of hydrophobic segments to hydrophilic segments. It can not only be evenly dispersed in water, but also significantly reduces the gas production problem during the slurrying of the negative electrode active material and the coating of the electrode, thereby improving the quality of the electrode and the performance of the battery.
[0130] The technical features of the above-mentioned embodiments can be combined arbitrarily. In order to make the description concise, not all possible combinations of the technical features in the above-mentioned embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0131] The above-described embodiments merely illustrate several implementations of the present invention, and while their descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the patent. It should be noted that a person skilled in the art would be able to make numerous variations and improvements without departing from the spirit of the present invention, all of which fall within the scope of protection of the present invention. Therefore, the scope of protection of the patent for this invention shall be determined by the appended claims.
Claims
1. A negative electrode active material, characterized in that The negative electrode active material includes a silicon-carbon material and a polymer coating layer coated on the surface of the silicon-carbon material, wherein the material of the polymer coating layer includes a binder and a hydrophilic grafting monomer; The side chain of the binder contains an end group capable of forming a hydrogen bond; any end group in the hydrophilic graft monomer structure contains a reactive group; the minimum unit repeating number of the segment in the side chain structure of the binder that does not contain an end group is n1, the minimum unit repeating number of the segment in the hydrophilic graft monomer structure that does not contain a reactive group is n2, and n1 / n2 is 1.5-9.5; The structural formula of the binder is shown in formula (1), , wherein R1 is selected from an unsubstituted alkyl chain, R2 is a carboxyl group, and n=100-800; The structural formula of the hydrophilic grafting monomer is shown in formula (2), , wherein R3 is selected from hydroxyl, primary amine, secondary amine or tertiary amine, and R4 is selected from unsubstituted ether chain.
2. The negative electrode active material according to claim 1, characterized in that The binder is connected to the hydrophilic grafting monomer through a chemical bond.
3. The negative electrode active material according to claim 1, characterized in that n1 / n2 is 1.5-5.
4. The negative electrode active material according to claim 1, characterized in that The binder is selected from at least one of polyvinyl acetic acid, poly (9-decenoic acid), and poly (2,2-tricosenoic acid).
5. The negative electrode active material according to claim 1, characterized in that The hydrophilic grafting monomer is selected from at least one of diethylene glycol monomethyl ether, tetraethyl glycol monomethyl ester, 2,5,8,11,14-pentaoxa-16-hexadecanol, undecaprylyl glycol monomethyl ether, and 1-(2-aminoethoxy)-2-methoxyethane.
6. The negative electrode active material according to any one of claims 1 to 3, characterized in that The polymer coating layer also includes a conductive agent.
7. The negative electrode active material according to any one of claims 1 to 3, characterized in that The silicon-carbon material is a composite material of porous carbon and nano-silicon, wherein the D min Greater than 0.3 μm, D 10 Greater than 1.5 μm, D 50 3.5μm-7μm, D 90 Less than 9μm, D max Less than 12μm, (D 90 -D 10 ) / D 50 Less than 1.1, average pore size 5nm-40nm; And / or, the median particle size of the silicon-carbon material is 5 μm-15 μm, and the particle size concentration is 0.5-1.5; And / or, the carbon content of the silicon-carbon material is 40%-60%; And / or, the specific surface area of the silicon-carbon material is 1.5m 2 / g-5m 2 / g; And / or, the resistivity of the silicon-carbon material is 2Ω·cm-10Ω·cm.
8. A method for preparing a negative electrode active material according to any one of claims 1 to 7, characterized in that: include: The silicon-carbon material, the binder and the hydrophilic grafting monomer are dispersed in a solvent to obtain a mixture, and the mixture is dried to obtain the negative electrode active material.
9. The method for preparing the negative electrode active material according to claim 8, characterized in that: The molar ratio of the side chain end groups of the binder to the hydrophilic grafting monomer is 1:0.2-1:1; and / or, the solid content of the mixture is 3%-40%; And / or, the mixture further includes a conductive agent; And / or, the drying method is selected from at least one of hot air drying, spray drying or vacuum drying; And / or, the drying temperature is 90°C-180°C.
10. A negative electrode plate, characterized in that: The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer, and the negative electrode active material layer includes the negative electrode active material according to any one of claims 1 to 7.
11. A battery, characterized in that: Comprising the negative electrode sheet as claimed in claim 10.
Citation Information
Patent Citations
Negative electrode binder and preparation method thereof, negative electrode plate and battery
CN116544409A
Cited By
Silicon-based negative electrode material and preparation method thereof, negative electrode plate and lithium ion battery
CN122091541A